Differentiation of human AB plasma hematopoietic stem/progenitor cells from peripheral blood into mature erythrocytes - Jiaojie WANG; Hong SHAN; Huijuan AN; Min LIU; Lili BIE; Xiaogai HAN; Jianbin LI (Zhongguo shuxue zazhi, 2022)
Objective To investigate the feasibility of differentiation of human AB plasma hematopoietic stem/progenitor cells (HSCs/HPCs) from peripheral blood into mature erythrocytes. Methods Hematopoietic stem/progenitor cells were induced to be differentiated into mature erythrocytes in the medium supplemented with 5% FBS, 3% FBS + 2% human AB plasma and 8% human AB plasma, respectively, and inoculated in 24-well culture plate at the density of 1×106/mL. Cell proliferation and morphological changes were observed in three different groups. Flow cytometry was used to detect erythroid terminal differentiation markers, i. e. GPA, Band3 and α4(α4-integrin), and late erythroid cell enucleation in different group. The effects of different culture conditions on HSCs/HPCs differentiation into mature erythrocytes were compared. Results The cell growth and proliferation multiples of the three groups (8% human AB plasma, 5% FBS and 3% FBS+ 2% human AB plasma) were 2 573±116 vs 2 514±246 vs 2 539±119(P>0.05), respectively. The morphological changes of the three groups were similar. With the extension of culture time, the cells differentiated from proerythroblasts to basophils, polychromatic erythroblasts and positive erythroblasts, and almost all of them differentiated into erythrocytes enucleation on day 21. GPA expression and enucleation rate(%) of the three groups were 97.17±1.91 vs 94.95±1.61 vs 96.15±1.38, and 85.1±3.26 vs 86.93±5.96 vs 86.5±3.36(P>0.05), respectively. Conclusion The differentiation of HSCs/HPCs from peripheral blood plasma into mature erythrocytes from human AB was similar to that of fetal bovine serum.